2008
DOI: 10.2215/cjn.02010507
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of the Prediction of Mortality in Hemodialysis Patients by Use of Cytokine Proteomic Determination

Abstract: Background and objectives: Inflammation-induced atherosclerosis and enhanced susceptibility to infection are linked to immune dysfunction and account for an important part of mortality in hemodialysis patients. This 4-yr prospective study aimed to use cytokine proteomic determination for predicting cardiovascular and noncardiovascular mortality in hemodialysis patients.Design, setting, participants, & measurements: Levels of 12 cytokines were measured using a proteomic biochip system in 134 patients who were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Inflammation has been recognized as an important predictor of morbidity and mortality in uremic patients and is strongly associated with cardiovascular disease [8][9][10]. In concordance with previous analyses, we found that high CRP was a risk factor in our dialysis population [13,31,32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Inflammation has been recognized as an important predictor of morbidity and mortality in uremic patients and is strongly associated with cardiovascular disease [8][9][10]. In concordance with previous analyses, we found that high CRP was a risk factor in our dialysis population [13,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…Modalities of recruitment and followup have been previously described [10,12,13]. Patients free of symptoms or signs of acute inflammatory or infectious diseases were included and were followed up prospectively yearly until 1 January, 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, the Evidence Investigator biochip system (Randox) method allows the simultaneous determination of cytokines, cytokine receptors and growth factors, over five multianalyte arrays. The combination of highly specific antibodies and advanced chemistries enables multiple cytokines and growth factors to be detected simultaneously in a single sample [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL)-6 and anti−/pro-inflammatory cytokine balance expressed as (IL-4 + IL-10)/IL-6 ratio were associated with an enhanced hazard ratio of cardiovascular mortality in HD patients [2]. Functional imbalance between regulatory T cells and T helper (Th) cells was also found as a contributor to the high incidence of cardiovascular events in this group [3].…”
Section: Introductionmentioning
confidence: 99%